Enhancing medication adherence in older adults at two nurse practitioner–owned clinics. Issue 7 (6th July 2021) - Kulsick, Cecily; Votta, Jennie; Wright, Wendy L.; White, Patricia; Strowman, Shelley
ABSTRACT: Background: The World Health Organization identified medication adherence as the greatest opportunity to improve outcomes related to chronic disease. Adherence rates of 80% or greater, or taking medication as prescribed at least 80% of the time, can positively impact health outcomes. Local problem: A prior study at two nurse practitioner (NP)–owned family practice clinics in New Hampshire measured medication adherence among adult type-2 diabetes mellitus (DM) patients at 77% and declining over a 4-year period. Patients' hemoglobin A1c rates were stagnant despite previous initiative to improve this biomarker. Methods: Nurse practitioners were educated on provider-driven strategies to improve medication adherence in the older adult with DM, hypertension, and hyperlipidemia. A review of medical records was performed on patients for 52 weeks before seminar and 13 weeks after seminar to capture medication adherence rates and clinical biomarkers. Intervention: Pre- and postseminar data were analyzed to determine whether the seminar resulted in improved adherence and clinical outcomes. Results: Preseminar medication adherence rates exceeded evidence-based standards of 80% for each condition. Postseminar, statistically significant improved adherence rates were seen among DM patients with hypertension. Adherence worsened among hyperlipidemia patients, although this change was not statistically significant. Clinical biomarkers saw little change. Conclusions: This quality improvement project found that educating NPs on strategies to improve medication adherence can improve adherence among DM and hypertension patients. Continued education and measurement of adherence and clinical biomarkers are encouraged to capture more postseminar visits. This project adds to the growing body of knowledge about patients managed by NPs and NP-owned practices.